Rock mechanics on a geological base - Pusch, Roland (Elsevier, 1995)
Until a few years ago, hydropower, road tunneling and mining were the main fields interested in rock mechanics. Now, however, rock mechanics is becoming increasingly important in many more branches - the most significant globally being the disposal of hazardous, especially radiaoctive, waste in deeply located repositories. This has raised a number of new aspects on the mechanical behaviour of large rock masses hosting repositories and of smaller rock elements forming the nearfield of tunnels and boreholes with waste containers. The geological background and above all rock structure form the basis of this book. The structural scheme proposed is referred to explain the scale-dependent behaviour of rock. Thus, the reason for differences in strength and strain properties of different types and volumes of rocks is shown in a very clear fasion, using simple material models and very basic numerical models. The author's academic background in both geology and soil and rock mechanics and his long experience in practical design and construction work has led to an unusually pedagogic way of dealing with the subject. The book is intended for use by consultants in engineering geology and waste disposal and by students of these subjects. However, engineers and geologists with a limited background in stress/strain and fracture theory and computer-based calculation methods will also find the book attractive.
Keywords: Rock mechanics.; Engineering geology.; elektronické knihy; electronic books